Measurements and Analysis of Polycyclic Aromatic Hydrocarbons near a Major Interstate - Dennis K. Mikel; Viney P. Aneja (Atmosphere, 2016)
Polycyclic aromatic hydrocarbons (PAHs) were measured near Interstate 40, just east of Research Triangle Park, North Carolina, USA. The goals of this project were to ascertain whether a sufficient quantity of PAHs could be collected using low flow (16.7 L/minute) over 8-h periods and if so, do investigate how the PAHs correlate to local sources, atmospheric pollutants and meteorology. The 8-h integrated samples were collected on 20 sampling days over a two month period during fall 2014. The samples were collected using low flow (BGI Incorporated PQ200) fine particulate samplers analyzed using gas chromatography-mass spectrometry (GC-MS). Temporal distributions of the PAHs (average mean 9.2 nanogram/cubic meter ±9.0 std) were compared to traffic count, and meteorological and pollutant data collected at the near roadway station. Using the meteorological data (i.e., wind speed and direction vector data), wind roses were created illustrating the local sources of the PAHs. In terms of correlation to atmospheric oxidants, (i.e., ozone, nitrogen dioxide and nitric oxide) wind rose analysis illustrated the morning hours which were predominantly southern winds, while the afternoon hours illustrated southerly and easterly winds, which suggests that the automobile traffic is the main source of PAHs. The nighttime hours wind rose shows winds from the northerly and easterly direction, which are predominantly from the RDU International Airport. Since the wind direction vectors illustrated that the afternoon hours (i.e., 12 p.m. to 8 p.m.) were from the interstate, comparisons were performed on the samples collected in this time period for both the traffic and pollutant data. The comparison of the traffic data showed a correlation with the number of vehicles (>60 feet i.e., heavy duty diesel engine vehicles). In addition, with the ozone, nitrogen dioxide and nitric oxide) there is a significant linear correlation between the sum of the measured PAHs with nitric oxide (NO), nitrogen dioxide (NO2) and ozone (O3) with the R2 values being 0.1, 0.04 and 0.07 respectively. An analysis of variance (ANOVA) statistical regression was performed on the pollutant data versus the measured sum of the PAHs. With the alpha set at 0.05, (α = 0.05) the p-values for O3, NO2 and NO were 0.00613, 0.000496 and 0.000264, respectively, which are significant. In addition, the PAH concentration found in this study compare favorably to other published studies (0.1 to 193.6 ng/m3) both nationally and internationally.